Coordination chemistry of guanidine derivatives - Moore, Charles H. M. (1987)
This thesis describes an investigation of the coordination chemistry of l-cyanoguanidine (cnge), l-carbamoylguanidine (clge) and l-amidino-O-ethylurea (aOeu). Various copper(II) complexes of these analogous molecules were synthesised and characterised using mainly X-ray crystallographic and spectroscopic (infrared and UV-visible) techniques. Only bis (cnge) complexes were observed for copper(II) ions. The monodentate cnge ligands coordinated the copper(II) via their nitrile nitrogen atoms which were located in trans equatorial positions of the copper(II) ions's tetragonally distorted octahedral coordination sphere. Comparison of the infrared spectra of the complexes with that of cnge indicated that the spectra were highly diagnostic of coordination to the copper(II) ion. Clge exhibited amphoteric properties; the neutral, anionic and cationic derivatives formed complexes with the copper(II) ion. Whereas the former pair gave bis chelate complexes, the latter derivatives acted merely as a cation and was remote from the copper(II) ion's coordination sphere. Complexation of the neutral molecule resulted in a proton transfer from a terminal amine group to a central nitrogen atom permitting chelation via an imine nitrogen atom and a carbonyl oxygen atom to give a square planar CUN2O2 chromophore. The structural ramifications of this tautomeric shift were near identical to those observed upon cation formation which occurred by protonation of the central nitrogen atom of the uncoordinated neutral molecule. Unequivocal structural data could not be obtained for the complex of the anionic derivative. Spectroscopic analysis indicated, however, that chelation occurred via two imine nitrogen atoms to give a square planar CuN4 chromophore. Ethanolysis of cnge was effected in the presence of copper(II) ions and ethanol producing complexes of aOeu with a metal:ligand ratio of 1:1 or 1:2. In both complexes the ligand(s) chelated the copper(II) ion via two imine nitrogen atoms. The former complex, a dimer, exhibited a square pyramidal CUN2X3 chromophore (X=Cl,Br) whilst the latter complex was a bis chelate with a square planar CUN4 chromophore. Monitoring the Uv-visible and infrared spectra of ethanol solutions containing copper(II) chloride and cnge, indicated the presence of a plethora of reactions. However, it was concluded that initially mono and/or bis(cnge)copper(II) complexes, of low stability, were present in equilibrium with the reactants. Subsequently, ethanolysis of coordinated cnge occurred producing mono(aOeu)copper(II) complexes. Series first order kinetics approximated to those of the ethanolysis reaction. The ethanolysis process was then repeated to give the final product a bis(cnge)copper(II) complex.